Straight from the Horse’s Mouth: A Case Study on the Adult Male Fans of My Little Pony - Schimpf, Kaitlyn Elizabeth (MacEwan University Student eJournal, 2015)
This is a qualitative case study that examines an alternative subculture composed of adult males who are fans of the Hub Network cartoon television series: My Little Pony: Friendship is Magic. Given the predominantly female cast of pony characters who primarily serve as positive role models for children, the fan base, which refers to itself as "bronies", provides a unique opportunity to explore a group that defies traditional norms regarding masculinity. Four main themes were explored. First, this study seeks to explain why adult males are drawn to this particular show. In addition, this study explores how the bronies are perceived by others who are not part of this subculture. Since it is presumed that bronies are regarded in a negative manner by outsiders, this study also attempts to explain how bronies deal with these primarily negative perceptions. Finally, this study examines how a sub-group within the fan base who derive sexual pleasure from the pony characters differ from the more mainstream group of bronies.  Bronies make for a fascinating subculture when framed within gender and sexuality in the age of the internet. Content analyses and narrative analyses were employed using a variety of data sources including online message boards specially created by fans to discuss the television series, popular new stories and a documentary on the bronies subculture. While unusual, the bronies, for the most part, appear to be a harmless group of males who are brought together by a common interest in a cartoon that promotes friendship and acceptance and many inadvertently help to break down traditional stereotypes.